Viking Age textiles and tapestries: Drawings by Miranda Bødtker - Jørgensen, Lise Bender; Moe, Dagfinn; Lukesova, Hana (Archaeological Textiles Review, 2021)
For many years, illustrator Miranda Bødtker (1896–1996) made drawings for botanists, zoologists and archaeologists at Bergen Museum, the University of Bergen in Norway. After her death, thousands of drawings were discovered as part of her estate. Among them were numerous unpublished drawings of archaeological textiles from five sites. Bødtker’s illustrations show that although several scholars have studied the textiles, none had seen them all. This includes textiles from two Viking Age burials, Grønhaug and Dale, both of which comprise remains of tapestries hardly mentioned in the archaeological literature. This paper presents Bødtker’s drawings of textiles from these two sites and discusses how they compare with published descriptions and new photos of the textiles, with drawings of textiles from the Oseberg burial, and to what degree this form of documentation meets current scientific demands.